A study on the relationship between metabolism of Cyanobacteria and chemical oxygen demand in Dianchi Lake, China. (21st July 2019) - He, Jia; Zhang, Ying; Wu, Xue; Yang, Yan; Xu, Xiaomei; Zheng, Binghui; Deng, Weiming; Shao, Zhi; Lu, Lu; Wang, Li; Zhou, Hongbin
Abstract: Recent increases in concentrations of chemical oxygen demand (COD‐Cr) in Dianchi Lake, China, is an important factor affecting its water quality. Large volumes of cyanobacteria algae have also been recorded in this lake; its growth, distribution and metabolism are believed to directly or indirectly affect water quality. The relationship between metabolism of cyanobacteria and COD‐Cr in Dianchi Lake, and the causes of this relationship, are examined in this study. Results show that the increase of COD‐Cr concentration is closely related to the metabolism of algae, and that organic substances containing nitrogen and sugars, produced by metabolism, contribute to an increase of COD‐Cr to a certain extent. The characteristics of fluorescence spectra of dissolved organic matter (DOM) in the Waihai area of Dianchi Lake are similar to those of algae culture water, and their dominant substances are protein‐like substances. Algae release organic substances into water during its growth cycle and extracellular organic substances are mainly released during its normal growth and metabolism stages. Once algae cells enter the decline stage, internal organic matter is released during the dying and decomposition stages, resulting in a distinct increase of COD‐Cr. A high concentration of organic matter is present in Dianchi Lake sediments, dominated by native organic matter predominantly derived from aquatic plants and plankton. This finding indicates a potential long‐term risk of organic pollutants being released from dead algae cells into the lake. Practitioner points: There is a distinct positive correlation between COD‐Cr and Chl‐a concentration in Dianchi Lake. Organic substances containing nitrogen and sugars produced by algae metabolism contributed to COD‐Cr. The cells die and decompose organic matter content in the water substantially increases, resulting in a distinct increase of COD‐Cr. Weight >20 kDa are mainly released into the water body during the decomposition of algae cells after mortality. Organic matter content in the water substantially increases, resulting in a distinct increase of COD‐Cr. Abstract : It was observed that the increase of COD‐Cr concentration in Dianchi Lake is closely related to the metabolism of cyanobacteria. The cyanobacteria release organic substances into water during its whole growth cycle. The major constituent of the organic substances are protein‐like substances. Even after mortality and deposition of algae cells, there is still the risk of organic pollutants being released from the dead algae cells into the lake.